2014
DOI: 10.1002/meet.2014.14505101114
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing chinese‐english mixed language queries in a web search engine

Abstract: With the increasing number of multilingual web pages on the Internet, multilingual information retrieval has become an important research issue. While queries are the key element of information retrieval process, mixed‐language queries have not yet been adequately studied. This study investigates the search topics and user intents of Chinese‐English mixed language queries submitted to a Chinese web search engine, and develops a typology of English terms used in those mixed language queries. The preliminary fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The analysis of interview data found that Chinese-English mixed language queries are used mainly for four types of search: recreation, work-related, academic and daily life. This is consistent with findings of previous query log analysis (Fu and Wu, 2014). Recreation searching included, but was not limited to, looking for a specific celebrity, place, book, movie, game, brand, recipe, sport, product or company originating in the Anglosphere.…”
Section: Resultssupporting
confidence: 85%
“…The analysis of interview data found that Chinese-English mixed language queries are used mainly for four types of search: recreation, work-related, academic and daily life. This is consistent with findings of previous query log analysis (Fu and Wu, 2014). Recreation searching included, but was not limited to, looking for a specific celebrity, place, book, movie, game, brand, recipe, sport, product or company originating in the Anglosphere.…”
Section: Resultssupporting
confidence: 85%
“…However, very few studies have addressed why and how people use mixed language queries in web searching. In our previous studies, we examined the topics and user intents of Chinese-English mixed language queries, and developed a typology of English terms used in those queries [3,4]. In this poster we report the findings about the context (i.e., activities) in which users employed Chinese-English mixed language queries and why they preferred to those queries.…”
Section: Introductionmentioning
confidence: 97%